On the identity of Benglebra Mahmood & Ahmad, and other Mukariini (Hemiptera: Cicadellidae: Deltocephalinae) from Bangladesh and Pakistan - Khatri, Imran; Webb, Michael D. (Zootaxa, 2011)
The leafhopper tribe Mukariini (Deltocephalinae) is newly recorded from Pakistan and Bangladesh. Members of the tribe are reviewed including the genus Benglebra Mahmood & Ahmed 1969 from Bangladesh, which was previously placed in Typhlocybinae, new placement. The identities of its two included species, B. alami Mahmood & Ahmed and B. bipunctata Mahmood & Ahmed are discussed, and their types re-examined and illustrated. Two other, included and figured, Mukariini newly recorded from Bangaldesh and Pakistan are: Mukaria splendida Distant and Flatfronta sp., respectively. Hussainiana tripunctata Mahmood & Ahmed 1969 is synonymised with Kolla ceylonica Melichar 1903, syn. nov., of the subfamily Cicadellinae, resulting in the synonymy of Hussainiana with Kolla Distant 1908, syn. nov.